2016
DOI: 10.1371/journal.pone.0152729
|View full text |Cite
|
Sign up to set email alerts
|

The qEEG Signature of Selective NMDA NR2B Negative Allosteric Modulators; A Potential Translational Biomarker for Drug Development

Abstract: The antidepressant activity of the N-methyl-D-aspartate (NMDA) receptor channel blocker, ketamine, has led to the investigation of negative allosteric modulators (NAMs) selective for the NR2B receptor subtype. The clinical development of NR2B NAMs would benefit from a translational pharmacodynamic biomarker that demonstrates brain penetration and functional inhibition of NR2B receptors in preclinical species and humans. Quantitative electroencephalography (qEEG) is a translational measure that can be used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
(38 reference statements)
2
19
0
Order By: Relevance
“…This action of NMDAR blocker may be specifically related to receptor blockade or may relate to nonspecific actions on the neuronal dynamics during SE. NMDAR antagonists are known to affect EEG regardless of their ability to terminate SE . Indeed, in the current study, the power of EEG in certain frequencies was different between MK‐801‐treated and untreated animals.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This action of NMDAR blocker may be specifically related to receptor blockade or may relate to nonspecific actions on the neuronal dynamics during SE. NMDAR antagonists are known to affect EEG regardless of their ability to terminate SE . Indeed, in the current study, the power of EEG in certain frequencies was different between MK‐801‐treated and untreated animals.…”
Section: Discussionmentioning
confidence: 51%
“…NMDAR antagonists are known to affect EEG regardless of their ability to terminate SE. 28 Indeed, in the current study, the power of EEG Altered GABAergic transmission is proposed to play an important role in the disinhibition of DGCs during epileptogenesis. 29 The potential mechanisms contributing to the reduced GABAergic inhibition involve a loss of interneurons, the zinc-induced collapse of inhibition, and altered GABAR expression.…”
Section: Discussionmentioning
confidence: 67%
“…To facilitate the progression of BMS-986163, we examined effects on the qEEG. Previous studies have shown robust qEEG power band changes in monkeys treated with GluN2B NAMs (Keavy et al, 2016), and BMS-986163 produced the same pattern of response. As an approach, changes in qEEGrelated measures for NMDA receptor antagonists generally align well across species and, although not tested here, other measures such as auditory evoked potentials also have translational utility for GluN2B NAMs (Nagy et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…qEEG Studies in Cynomolgus Monkeys. Studies to examine the effect of GluN2B NAM treatment on the qEEG response were conducted by BMS using methods described previously (Keavy et al, 2016). Six cynomolgus monkeys served as subjects for the qEEG studies, and each had been used previously in pharmacological studies, with a drug-free period of at least 1 month prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…S tructure of Neurofeedback S ystem shooters [13]. Keavy et al suggested that neurofeedback could be used as a treatment, and although results using biofeedback cannot compete with drug therapy, there are significantly fewer side effects when it comes to ADHD therapy [14]. Zołubak et al proposed a prognostic expert system using neurofeedback signals, in which they addressed preliminary diagnostics issues using policy-based computing [15].…”
Section: Related Workmentioning
confidence: 99%